1988
DOI: 10.1002/j.2050-0416.1988.tb04578.x
|View full text |Cite
|
Sign up to set email alerts
|

Nisin and Brewing

Abstract: Nisin, an internationally accepted food preservative has been shown to inhibit the growth of almost all Gram-positive beer-spoilage bacteria investigated. The initial effects on these bac teria appear to be upon the cell membrane. Nisin has little effect on most Gram-negative bacteria and has no effect upon the growth and fermentation properties of brewing yeasts. Nisin activity survives kieselguhr filtration, fining and pasteurisation and has no effect on beer shelf life. Nisin has potential applications in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…lactis, known to be capable of producing nisin (NCIMB 8780, 8586, 701402 and 701403), and seven isolated strains of the same species found in the beverage environment (TUM 575, 8947, 8127, 8446, 8673, 8973 and 8872), were tested under typical brewery conditions. As in previous work, it was found, that all of the tested strains could be genetically differentiated via PCR-(GTG) 5 . In addition, the absence of the genes HorA, HorC and ORF5 indicated that all strains were sensitive to hop components.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…lactis, known to be capable of producing nisin (NCIMB 8780, 8586, 701402 and 701403), and seven isolated strains of the same species found in the beverage environment (TUM 575, 8947, 8127, 8446, 8673, 8973 and 8872), were tested under typical brewery conditions. As in previous work, it was found, that all of the tested strains could be genetically differentiated via PCR-(GTG) 5 . In addition, the absence of the genes HorA, HorC and ORF5 indicated that all strains were sensitive to hop components.…”
supporting
confidence: 74%
“…• Its implementation before pasteurization to save energy, costs and the risk of heat damage by reducing times and temperatures (5,3,8).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of nisin to the fermentations had no adverse effect on the taste of the beers 136 . However, the cost of the addition of nisin to all fermentations would be prohibitively expensive but perhaps it has a role if used as a remedial measure to treat contaminated fermentations 138 .…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Ogden et al 138 suggested that nisin could be added during fermentation, to prevent bacterial growth that may compete with the brewing yeast for nutrients. Alternatively, nisin could be used as a substitute for acid in breweries where yeast washing is practiced.…”
Section: Antifungal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation